2020
DOI: 10.3389/fenvs.2020.00126
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Boron Isotopes for Identifying Nitrogen Sources Supplied by Submarine Groundwater Discharge to Coastal Waters

Abstract: Stable isotopes of oxygen, nitrogen, and boron were used to identify the sources of nitrate (NO 3 −) in submarine groundwater discharge (SGD) into a large tidal estuary (Long Island Sound, NY, United States). Potential contaminants such as manure, septic waste and fertilizer overlap in δ 15 N and δ 18 O but have been shown to have distinctive δ 11 B in non-coastal settings. Two distinct subterranean estuaries were studied with different land-use up gradient, representative of (1) mixed medium-density residenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
(90 reference statements)
0
7
1
Order By: Relevance
“…An earlier study of boron that focused on sources of nitrate into the Long Island Sound via a subterranean groundwater discharge (SGD) found that δ 11 B combined with δ 15 N and δ 18 O of nitrates in water samples do not provide values that fit cleanly within the range of published values for its use as a tracer of nitrates [15]. However, while this study could not pinpoint specific sources, it did identify differences between the two study areas.…”
Section: Introductioncontrasting
confidence: 61%
See 1 more Smart Citation
“…An earlier study of boron that focused on sources of nitrate into the Long Island Sound via a subterranean groundwater discharge (SGD) found that δ 11 B combined with δ 15 N and δ 18 O of nitrates in water samples do not provide values that fit cleanly within the range of published values for its use as a tracer of nitrates [15]. However, while this study could not pinpoint specific sources, it did identify differences between the two study areas.…”
Section: Introductioncontrasting
confidence: 61%
“…However, while this study could not pinpoint specific sources, it did identify differences between the two study areas. These two areas, which were selected to represent agricultural (fertilizers and manure) vs. urban sources (septic and fertilizer), both showed a large range in δ 11 B [15]. The agricultural site had higher boron concentrations and lighter δ 11 B, while the urban source area had lower boron concentrations that trend toward the seawater δ 11 B value [15].…”
Section: Introductionmentioning
confidence: 99%
“…This interaction between the NO 3 − production and DOC supply reveals that the retention of NO 3 − in coastal systems might be higher than previously thought, since the SOM dependent NO 3 − removal capability tends to be stable during the high loading of bio-labile DOM. Within many coastal ecosystems, a large amount of terrestrial NO 3 − , derived from overuse of chemical fertilizer or leakage from sewage pipes, reaches the coastal seawater via the benthic system (Tamborski et al, 2020). Compared with seawater concentration, submarine groundwater discharge-derived NO 3 − concentration was several orders of magnitude higher at our site (e.g., more than 10 times higher in Sanggou Bay, China, Wang et al, 2014).…”
Section: Benthic N and C Interactions And Coastal Managementmentioning
confidence: 69%
“…Both dams effectively block saltwater intrusion into the watershed (Nawa and Miyazaki 2009). In the coastal areas, sea spray blown inland by lapping waves results in boron characteristics that are similar those of seawater (Tamborski et al 2020). We assume that the island region exhibits similar phenomena, wherein the endmember of groundwater includes the precipitation content of some seawater components.…”
Section: The Process Of Boron Migrationmentioning
confidence: 99%
“…Dissolved nitrogen has been utilized as a tracer of anthropogenic activities involving nitrogenous compounds (Yoshimoto et al 2013;Nakano et al 2013). However, using nitrogen as a single tracer has limitations, as the oxygen and nitrogen isotopic composition in nitrate ions cannot identify pollution sources (Tamborski et al 2020). To address this issue, combining nitrate with boron has emerged as a new way to achieve higher accuracy in pollutant identification (Widory et al 2005).…”
Section: Introductionmentioning
confidence: 99%